Principles of the UN Convention on the Rights of the Child - Wedeł-Domaradzka, Agnieszka (International Children's Rights, 2024)
This study focuses on the principles of the UN Convention on the Rights of the Child, which are regarded as interpretative principles concerning the rest of the Convention’s text. This means that states bound by the provisions of the Convention are obliged to consider them when applying legislation concerning specific facts related to the situation of children. The body of the study includes an analysis of the principles of non-discrimination, considering the best interests of the child, the right to survival and development, considering the view of the child, and related to the realisation of the right to be raised in a loving (in principle, own) family. The last principle is not directly contained in the body of the articulated Convention, but can be found in its preamble, which must also be considered as a determinant part of the interpretation of the provisions. The analysis of the individual principles focuses on the elements of their contents, and the development and safeguarding of their implementation by the other rights and obligations of the Convention incumbent on both parents and state parties. The paper concludes with assertions on ways to secure the optimal implementation of these principles.Keywords: children, Convention on the Rights of the Child, best interests of the child, nondiscrimination, survival and development of the child, view of the child, child’s rights